Political Discourse of Indonesian Raya Daily Newspaper in Indonesian Political Public Space 1955-1957 - Astana, Cornelius Bayu; Yuliantri, Rhoma Dwi Aria (Universitas Negeri Padang, 2024)
This research aims to examine the democratization process carried out by Indonesia Raya Newspaper through the political discourse raised and its role as a political public space in 1955-1957. The research method used is the historical method, which consists of 5 stages, namely topic selection, heuristics, verification, interpretation, and historiography. This research is supported by the theoretical framework of political public space to examine the role of Indonesia Raya Newspaper in raising political discourse and its function as a political public space. The results of this study show that (1) Indonesia Raya Newspaper practices personal journalism in its journalistic work so that the characteristics of the political discourse contained in its news are in line with the characteristics of its leader, Mochtar Lubis. (2) The role of Indonesia Raya Newspaper as a political public space is carried out by loading political discourse containing criticism of the government and politicians related to the social, political, and economic life of the community, which is published in the political section of Tajuk Rencana. (3) The process of forming political discourse is carried out using the investigative journalism method so that relevant topics are obtained. Topics found, such as indications of fraud in the 1955 elections and the controversy over the implementation of the KAA, were raised to become political discourses that affected the dynamics of Indonesian national politics at that time. Indonesia Raya Newspaper was able to play a role in Indonesia's democratization process by raising political discourse and providing political public space.